1990
DOI: 10.1111/j.1523-1739.1990.tb00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Viable Populations, Reserve Size, and Federal Lands Management: A Critique

Abstract: An examination of current viable population theories and reserve size studies suggests that biological diversity for North American national parks and forests is inadequately protected This conclusion is further supported by reviews of federal agency management plans and policies. Preservation of biodiversity is thwarted by lack of landscape–level management, insufficient data, competition between federal land management agencies, and bureaucratic inertia, among other factors. To dress these problems, an ecosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 18 publications
(16 reference statements)
4
28
0
3
Order By: Relevance
“…Unfortunately, for most of these and other pertinent questions there are no detailed guidelines. Even when there is some guidance (e.g., biogeography theory, population viability analysis, or metapopulation theory) the data needed for these more detailed evaluations are usually lacking (Grumbine 1990, Margules and Pressey 2000, Groves 2003. Expert opinion will therefore often play a major role in developing the conservation plan.…”
Section: An Overview Of Biodiversity Conservation Planningmentioning
confidence: 99%
“…Unfortunately, for most of these and other pertinent questions there are no detailed guidelines. Even when there is some guidance (e.g., biogeography theory, population viability analysis, or metapopulation theory) the data needed for these more detailed evaluations are usually lacking (Grumbine 1990, Margules and Pressey 2000, Groves 2003. Expert opinion will therefore often play a major role in developing the conservation plan.…”
Section: An Overview Of Biodiversity Conservation Planningmentioning
confidence: 99%
“…Through the development of PVA techniques, it became apparent that the size of a viable population is not static (Usher 1987, Menges 1990) but will differ according to the particular species (Gilpin and Sould 1986) and the circumstances impinging on that organism at any given time (Fowler and MacMahan 1982) and place (Grumbine 1990). This is because vulnerability to extinction will be, in part, related to demographic attributes and other characteristics (Howe and others 1991) and some of these will vary with environmental parameters that vary over time and space.…”
Section: Population Viability Analysis: a Review Estimating Viabilitymentioning
confidence: 98%
“…The more data the better for PVAs. Often such data are unavailable or incomplete (Grumbine 1990), in particular those for rare and endangered organisms that may urgently require PVA. Estimation of the values for modeled parameters requires experience and must be based on a detailed knowledge of the biology of a species or attributes of related taxa (Simberloff 1988).…”
Section: Limitations Of Population Viability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This so-called SLOSS controversy (Single Large Or Several Small), was an attempt to apply the theocy of island biogeography to resexve design (Noss 1989). Although this discussion centered largely on tests of the theory's predictions, it implied that biodiversity must not only be protected from habitat destruction but from all uses including hunting (Grumbine 1990 (1992) found that changes in species composition of passerine neotropical migrants were best explained by successional changes in the forest. pointed to intensive agriculture as the main factor in decline of the Bobolink (Dolichonyx oryzivorus) in the east.…”
Section: Introductionmentioning
confidence: 99%